Unraveling the Gonyaulax baltica Species Complex: Cyst–theca Relationship of Impagidinium variaseptum, Spiniferites pseudodelicatus sp. nov. and S. ristingensis (Gonyaulacaceae, Dinophyceae), With Descriptions of Gonyaulax bohaiensis sp. nov, G. amoyensis sp. nov. and G. portimonensis sp. nov. Issue 3 (27th March 2022) - Gu, Haifeng; Mertens, Kenneth Neil; Derrien, Amélie; Bilien, Gwenael; Li, Zhen; Hess, Philipp; Séchet, Véronique; Krock, Bernd; Amorim, Ana; Li, Zhun; Pospelova, Vera; Smith, Kirsty F.; et al.
Abstract : The taxonomy of the extant dinoflagellate genus Gonyaulax is challenging since its thecate morphology is rather conservative. In contrast, cysts of Gonyaulax are varied in morphology and have been related with the fossil‐based genera Spiniferites and Impagidinium . To better understand the systematics of Gonyaulax species, we performed germination experiments on cysts that can be identified as S. ristingensis, an unidentified Spiniferites with petaloid processes here described as Spiniferites pseudodelicatus sp. nov. and Impagidinium variaseptum from Chinese and Portuguese waters. Despite marked differences in cyst morphology, motile cells of S . pseudodelicatus and I. variaseptum are indistinguishable from Gonyaulax baltica . Motile cells hatched from S. ristingensis are morphologically similar to G. baltica as well but differ in the presence of one pronounced antapical spine. Three new species, Gonyaulax amoyensis (cyst equivalent S. pseudodelicatus ), Gonyaulax bohaiensis (cyst equivalent I. variaseptum ), and Gonyaulax portimonensis (cyst equivalent S. ristingensis ), were erected. In addition, a new ribotype (B) of G. baltica was reported from South Korea and a bloom of G. baltica ribotype B is reported from New Zealand. Molecular phylogeny based on LSU and SSU rRNA gene sequences revealed that Gonyaulax species with minute or short antapical spines formed a well‐resolved clade, whereas species with two pronounced antapical spines or lack of antapical spines formed the sister clade. Six strains of four above species were examined for yessotoxin production by liquid chromatography coupled with tandem mass spectrometry, and very low concentrations of yessotoxin were detected for one G. bohaiensis strain.